PEMANFAATAN PELAYANAN KESEHATAN OLEH PENDERITA TUBERKULOSIS PARU DI UPTD KESEHATAN PUSKESMAS SUKAMULYA KABUPATEN CIAMIS TAHUN 2015 - Yayu Handayani; Elis Noviati; Inna Sayyidatul Husna (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2017)
Pulmonary tuberculosisis an infectious disease remains a health problem in the community. Numbers of patient with pulmonary tuberculosis at Ciamis in 2013 is 1164 cases, in 2014 is 1388 cases and in 2015 is 1395 cases. UPTD Sukamulya routinely conducts health education with the aim of providing knowledge to the community. Health services at Sukamulya has a good services, but there are some peoples who feeling embrassed to check the disease in the health centre.This research used a descriptive method with the aim to describe an object of research. This research have a samples 30 respondent with instrument using a likert scale in the form of a check list with 16 questions.Based on the result of questionnaire analysis study from 30 respondents about the factors in the needs of health care utilization by patients with pulmonary tuberculosis has been showed that 4 patients with pulmonary tuberculosis (13,33%) utilize health care services properly, 25 patients with pulmonary tuberculosis (83,33%) is a harness of health care and one person wit sufficient pulmonary tuberculosis patients (3,34%) is underutilization of health services.Utilization of health services by patients with pulmonary tuberculosis at UPTD Puskesmas Sukamuya Ciamis is well done. Keywords: utilization of health services, tuberculosis, health centers